Subsurface hydrology of tile‐drained headwater catchments: Compatibility of concepts and hydrochemistry. Issue 9 (14th September 2021) - Van Stempvoort, Dale R.; MacKay, D. Ross; Koehler, Geoff; Collins, Pamela; Brown, Susan J.
Abstract: Concepts and terms used in previous multidisciplinary studies of tile‐drained aquitard‐dominated catchments (TDADC) are inconsistent and confusing. We provide a well‐defined, comprehensive conceptual model of the subsurface hydrology of TDADC by selecting seven mutually compatible and consistent concepts. These concepts are: (1) groundwater as the main source of baseflow in headwater streams, (2) dominance of 'pre‐event' water in stormflow, (3) importance of both macropores and matrix, (4) changes in flowpaths with rate of stream discharge, (5) dominance of shallow, lateral subsurface flow, (6) interactive nature of subsurface water, (7) transpiration of groundwater. This conceptual model was successfully 'field‐tested' by examining data collected in a TDADC in a rural area of southern Ontario, Canada. The data consist mainly of chemical and isotopes tracers in water samples (headwater streams, groundwater, precipitation, tile water, soil‐surface water), supplemented by water levels and meteorological data. Abstract : A well‐defined, comprehensive conceptual model of the subsurface hydrology of tile‐drained aquitard‐dominated catchments (TDADC) is provided by selecting seven mutually compatible and consistent concepts. This conceptual model was successfully "field‐tested" by examining data collected in a TDADC in a rural area of southern Ontario, Canada. The data consist mainly of chemical and isotopes tracers in water samples (headwater streams, groundwater, precipitation, tile water, soil‐surface water), supplemented by water levels and meteorological data.